
2个回答
展开全部
nPm=n(n-1)(n-2)(n-3).....(n-m+1)
nPn=n!,0!=1
nCm=nPm/mPm=n!/[m!(n-m)!]
nPm=n*(n-1)P(m-1)
nCm=nC(n-m)
(n+1)Cm=nC(m-1)+nCm
nC0+nC1+nC2+.....+nCn=2^n
k*nCk=n*(n-1)C(k-1)
nC0*nCn+nC1*nC(n-1)+...+nCn*nC0
=nC0*nC0+nC1*nC1+.....+nCn*nCn=(2n)Cn
kCk+(k+1)Ck+(k+2)Ck+...+nCk=(n+1)C(k+1)
nPn=n!,0!=1
nCm=nPm/mPm=n!/[m!(n-m)!]
nPm=n*(n-1)P(m-1)
nCm=nC(n-m)
(n+1)Cm=nC(m-1)+nCm
nC0+nC1+nC2+.....+nCn=2^n
k*nCk=n*(n-1)C(k-1)
nC0*nCn+nC1*nC(n-1)+...+nCn*nC0
=nC0*nC0+nC1*nC1+.....+nCn*nCn=(2n)Cn
kCk+(k+1)Ck+(k+2)Ck+...+nCk=(n+1)C(k+1)
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询